The Prognostic Value of Histopathological Features in Early-Stage Mycosis Fungoides: Insights from a Retrospective-Prospective Cohort Study - Sandra Jerkovic Gulin; Ivana Ilic; Romana Ceovic (MDPI AG, 2024)
Primary cutaneous lymphomas (PCLs), especially mycosis fungoides (MF), pose significant diagnostic and therapeutic challenges. This study aims to correlate initial histological features with the disease course and survival in MF patients. A retrospective-prospective cohort study was conducted on 83 patients diagnosed with early-stage MF at the Departments of Dermatovenerology and Pathology, UHC Zagreb, from January 2003 to December 2012. The analyzed histopathological parameters included lichenoid dermal lymphocyte infiltrate, Pautrier microabscesses, and lymphocyte atypia. Patients with more than 30 guardian lymphocytes per 100 keratinocytes exhibited worse overall and progression-free survival. Furthermore, those with over 50% atypical lymphocytes demonstrated a faster progression rate. A dense lichenoid dermal infiltrate and a high count of lymphocyte "keepers" significantly increased the mortality risk within five years of diagnosis. This study did not fully confirm the hypothesis regarding the prognostic value of large Pautrier microabscesses but highlighted the importance of dense lichenoid infiltrates. The study identified new potential histopathological prognostic factors in early-stage MF, suggesting the need for larger studies to confirm these findings. The identification of such predictors could enhance the prognostic stratification and guide more tailored therapeutic approaches for MF patients.